Soziale Normen, Akzeptanz von Innovationen und die moderierende Rolle von Trendsetting - Gunnesch-Luca, George; Klöble, Ulrike; Moser, Klaus; Göritz, Anja (Zeitschrift für Arbeits- und Organisationspsychologie, 2013)
Trendsetters are individuals who like to take up information on innovation and pass it on and explain it to others (Batinic et al., 2006). Trendsetting supposedly explains the diffusion of innovations because it describes individuals that are sensitive to innovations and less susceptible to social influence. However, contrary to these expectations, previous research has suggested that trendsetters strongly rely on social norms. This cross-sectional study - based on a sample of experts (n = 90) on agricultural innovations - analyses the effect of trendsetting, social norms, and their interaction on the acceptance of new technologies and innovations in precision farming. Consistent with results from an earlier study, trendsetters tend to take into account the attitudes of other persons when dealing with new technologies, and trendsetting seems to have a norm reinforcing function. Contrary to expectations, trendsetting does not seem to be a measure to identify individuals who are both high in innovativeness and less affected by the opinions of other people.
Keywords: trendsetting; diffusion of innovations; precision farming; technology acceptance